THE EFFECT OF INFLATION, EXPORT AND IMPORT ON ECONOMIC GROWTH IN CENTRAL JAVA - Silvia Hendrayanti; Zumrotun Nafiah; siti Aminah (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Economic growth is one of the indicators used to measure the success rate of a region's development. The purpose of this study is to determine the effect of inflation, exports and imports on economic growth in Central Java Province. The type of data used is monthly time series data from January 2017 to December 2021. The number of samples used is 60 samples. The analytical method used is multiple linear regression analysis.The results of the data processing carried out, the t test on the inflation variable shows a positive but not significant relationship to economic growth. This is based on a probability value greater than 0.05, namely 0.0731. For the export variable, the probability value is 0.0186, which means that the export variable has a negative and significant effect on economic growth. As for the import variable, the probability value is 0.0000. So that it can be interpreted that the import variable has a positive and significant influence on economic growth. From the results of this study, it is suggested that the government be able to implement policies to control inflation and apply export restrictions and increase imports while still paying attention to price balance and people's needs.